Profile of Thematic Learning Viewed from STEAM in the 2013 Curriculum for Grade IV Elementary School - Kurniati - Fadhilah; Fenny Roshayanti; Veryliana Purnamasari (Universitas Pendidikan Ganesha, 2021)
Education in Indonesia is still relatively low, because students have not been able to face the challenges of the industrial revolution 4.0. There needs to be an educational concept that is able to answer the challenges of the industrial revolution 4.0, one of which is STEAM (Science, Technology, Engineering, Art, Mathematics). This study aims to analyze the potential of STEAM contained in the Teacher's Book and Student's Book Theme 1-9 Revised 2017 grade IV Elementary School. This research is a qualitative descriptive study with the object of research directed to find out the potential of STEAM contained in the 2017 Revised Teacher's Book and Student's Book for Grade IV Elementary School. Data obtained from secondary data in the form of Teacher's Books and Revised 2017 Student Books for Class IV Elementary Schools that have been analyzed. The data collection method used the documentation analysis method so that the researchers analyzed the Theme Books 1-9 Class IV Elementary School. The data analysis method used is the Miles and Huberman model starting with data collection, data presentation, data reduction, and drawing conclusions and verification. The results show that there are facts that have STEAM potential and facts that have STEAM potential with an average of 80% of STEAM potential from the number of lessons in Themes 1-9. So, the results of the analysis of the 2017 Revised Teacher's Book and Theme Book for Grade IV Elementary School have the potential for STEAM. However, there are some learnings that do not have STEAM facts, so the learning does not have STEAM potential.